PENAMPILAN 19 GALUR GANDUM (Triticum aestivumL.) DI DATARAN MENENGAH, DESA SIDOREJO KIDUL, KECAMATAN TINGKIR, KOTA SALATIGA - Eko Budi Prasojo; Dina Banjarnahor (Agric, 2018)
The research toward 19 genotypes of wheat (Triticum aestivum L.) in medium plain has been done on May – September 2016. In Sidorejo Kidul Village, Tingkir Sub-district, Salatiga City, Central Java Province. The height of this plain is ±550 min above of sea surface. The purpose of the researcher is to know the appearance and the result potency of 19 genotypes of wheat in the medium plain in dray season and to get genotype which has better result in medium plain in dray season. This research is done in form of experiment in open land. The experiment is arranged based on Group Random Plan (GRP) by planting 19 genotypes in three land plot. Genotype is a treatment and land plot is a group. Growth can be seen from the blooming time, the height of the plant, harvest time and the sum of plant in each clump. While the appearance of the result the length of malai, the sum of spikeler in each malai, the sum of seed in each malai, the weight of 1000 seeds, the weight of seed in each m2 and the weight of 1 liter of seed. The result estimation is based on the length of malai, the sum of spikelet in each malai and the sum of seed in each malai.Obtained genotypes QUAIU, WBLL * 2KURUKU, PRL / 2 * PASTOR, O / HP-82-A-15-1-4, O / HP-12-A1-1-9, O / HP-78-A22-3- 7, O / HP-6-A8-2-10, O / HP-22-A27-1-10, O / HP-12-A5-1-3, O / HP-12-A5-4-5, O / HP-82-A15-2-3, Guri 3 and Guri 5. Thirteen genotypes have good yields in research.